Diagnostic accuracy of the latest-generation digital PET/CT scanner for detection of metastatic lymph nodes in head and neck cancer - Butt, Frederick; Dominguez-Konicki, Lillian; Tocci, Noah; Paydarfar, Joseph; Seltzer, Marc; Pastel, David (Frontiers in Nuclear Medicine, 2023)
Purpose: The aim of this retrospective analysis is to assess the diagnostic accuracy of a latest generation digital PET/CT scanner in the detection of cervical lymph node metastasis in patients undergoing staging work-up for head and neck cancer. Materials and Methods: 55 consecutive head and neck cancer patients at our institution who had a PET/CT after installation of a latest generation PET/CT (Siemens Biograph Vision) who subsequently underwent surgical neck dissection were included. The nodal station location and number of reported PET/CT positive metastatic lymph nodes was compared to a gold standard of final surgical pathology following neck dissection. Results: 188 neck levels and 1373 lymph nodes were resected. 56 neck levels (118 nodes) in 31 patients (56%) contained nodal metastases on surgical pathology. On a nodal level-by-level analysis, the overall sensitivity for detection of lymph node metastases on the latest generation PET/CT scanner was 96.4% and the specificity was 86.4%. The sensitivity and specificity for neck side analysis were 94.0% and 63.7%, and for individual patient analysis were 100% and 71%, respectively. Conclusions: In this single institution study, latest generation PET/CT had a high sensitivity and moderate to high specificity for detecting cervical node metastasis in head and neck cancer. Compared to data from older generation older generation PET/CT scanners, sensitivity of latest generation PET/CT was slightly higher, while specificity was similar to or slightly lower. Physicians involved in the management of head and neck cancer should be aware of possible changes in overall diagnostic accuracy when changing to a LG PET/CT scanner.